Recycling of waste and downgrading of secondary resources in a classical type of production model - Eiji B Hosoda (Journal of Economic Structures, 2012)
This paper analyses recycling of waste and downgrading of secondary resources using a classical type of production model represented by a Sraffian model. Residuals emitted as waste by households and secondary resources obtained by recycling of waste are negatively or positively priced, depending upon technological conditions and income distribution. In other words, they can be commodities (goods) or discommodities (bads), and the distinction cannot be determined by physical characteristics. How such distinction comes about is explained, based upon an interindustrial relationship and the choice of technique. It is also demonstrated that per capita consumption may not necessarily be a decreasing function of a growth rate. This is an anomaly which cannot be found in the economy where discommodities or bads are not explicitly considered.
Keywords: E11; O41; Q53; 330; commodity; discommodity; recycling; downgrading; choice of technique